2015
DOI: 10.1016/j.jcp.2015.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Numerical time-step restrictions as a result of capillary waves

Abstract: 22.04.15 Kb. Ok to add published version to spiral, OA pape

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
76
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 48 publications
2
76
0
Order By: Relevance
“…In a previous study on the dynamics of solitary waves on inertia-dominated falling liquid film of Denner et al [37], the results obtained with the DNS framework [47][48][49] used in this study showed excellent agreement with experimental measurements [6]. We propose a novel scaling for solitary waves, which we derive from the Nusselt flat film solution based on the physical mechanisms that underpin the growth and dispersion of solitary waves.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…In a previous study on the dynamics of solitary waves on inertia-dominated falling liquid film of Denner et al [37], the results obtained with the DNS framework [47][48][49] used in this study showed excellent agreement with experimental measurements [6]. We propose a novel scaling for solitary waves, which we derive from the Nusselt flat film solution based on the physical mechanisms that underpin the growth and dispersion of solitary waves.…”
Section: Introductionsupporting
confidence: 75%
“…We note that the transverse dimension is resolved with only one mesh cell, so that the simulation can be regarded as being effectively two-dimensional. The numerical time-step applied in the simulations satisfies a Courant number of Co = ∆t u |u|/∆x ≤ 0.25, as well as the capillary time-step constraint proposed by Denner and van Wachem [49].…”
Section: Setup Of the Numerical Experimentsmentioning
confidence: 99%
“…The computational domain is represented by an equidistant Cartesian mesh with a resolution of 10 cells per film height h N . The time step t satisfies a Courant number of Co = |u| t/ x 0.25 as well as the capillary time-step constraint derived by Denner & van Wachem (2015). The properties of the liquid film are directly taken from the experimental measurements (see § 3.4) and the gas phase is assumed to be air with density ρ g = 1.205 kg m −3 and viscosity µ g = 1.82 × 10 −5 Pa s. At the bottom (liquid-side) wall a no-slip condition is enforced and at the top (gasside) boundary a free-slip wall is applied.…”
Section: Simulation Set-upmentioning
confidence: 99%
“…Here the full Navier-Stokes equations are solved with appropriate 95 boundary conditions applied at the deforming interface between layers and at the free surface. Alternatively the Volume of Fluid (VOF) method, popular in multiphase CFD, may be used to obtain the film surface by solving a convection equation for an indicator function as recently examined in numerical experiments of vertically-falling films [31].…”
mentioning
confidence: 99%
“…The single nonlinear function C, representing the the integrated continuity equation with parabolic forms for the velocity and temperature, depends on h and all other the coeffi-240 cients in (30) and (31).…”
mentioning
confidence: 99%